Low-temperature intrinsic plasticity in silicon at small scales. (December 2018) - Merabet, A.; Texier, M.; Tromas, C.; Brochard, S.; Pizzagalli, L.; Thilly, L.; Rabier, J.; Talneau, A.; Le Vaillant, Y.-M.; Thomas, O.; Godet, J.
Abstract: The mechanical properties of materials usually depend on the size of the considered object. Silicon, for instance, undergoes between the macroscopic and nanometer scales, a brittle-to-ductile transition at room temperature. Although essential for the constantly developing Si-based nanotechnologies, the origin of this remarkable behaviour change remains undetermined for several years. The observation of the mechanisms responsible for plastic deformation in nano-objects is indeed highly challenging at the microscopic scale. One needs controlling the deformation while identifying induced individual plastic events at the smallest scale during the first stages of plasticity. This work describes nano-compression experiments on 100 nm-diameter Si nanopillars followed by post-mortem analysis of the deformed specimens through SEM and atomic resolution TEM imaging. The observed plastic deformation disrupts the usual description of low-temperature undissociated-dislocations-mediated plasticity and is comforted by molecular dynamics calculations. These results shed a new light on the transition between ductile and brittle regimes in silicon by introducing the missing link between plasticity and fracture. Graphical abstract: Image 1